Strategi Komunikasi Pemasaran Digital dalam Meningkatkan Brand Awareness Hotel AP Premier Batam Pasca Rebranding - Mutia Anjani; Riswandi Riswandi (Commed Jurnal Komunikasi dan Media, 2026)
The increasingly competitive hotel industry in Batam City prompted AP Premier Batam Hotel, formerly Travelodge Batam, to undertake a rebranding initiative in 2023 to strengthen its brand image and market competitiveness. This study examines the digital marketing communication strategy implemented through Instagram to enhance brand awareness after rebranding, as well as the supporting and inhibiting factors influencing its implementation. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving parties responsible for managing the hotel’s digital marketing activities. The analysis was conducted by relating the findings to the concepts of digital marketing communication, New Media theory, brand awareness, and the AISAS model (Attention, Interest, Search, Action, and Share). The results show that the Instagram-based digital marketing strategy focuses on consistent visual content, optimization of platform features such as Feeds, Stories, and Reels, and active audience engagement, which contributes to increased brand awareness, particularly at the brand recognition level. Supporting factors include content quality, audience engagement, and effective use of Instagram analytics, while inhibiting factors consist of limited resources, algorithm changes, and intense competition on social media.